Inhibition of iron and copper uptake by iron, copper and zinc - MIGUEL ARREDONDO (Biological Research, 2006)
Interactions of micronutrients can affect absorption and bioavailability of other nutrients by a number of mechanisms. In aqueous solutions, and at higher uptake levels, competition between elements with similar chemical characteristics and uptake process can take place. The consequences of these interactions may depend on the relative concentrations of the nutrients. In this work, we measure the effects of increasing concentrations of iron, zinc, and copper on iron and copper uptake in Caco-2 cells. Intracellular Fe or Cu levels were affected by incubating with increased concentrations of metals. However, when the cells already had different intracellular metal concentration, the uptake of Fe or Cu was nor affected. In competition studies, we showed that Cu and Zn inhibited Fe uptake, and while Fe inhibited Cu uptake, Zn did not. When the three metals were given together (1: 1: 1 ratio), Fe or Cu uptake was inhibited ~40%. These results point to a potential risk in the absorption and bioavailability of these minerals by the presence of other minerals in the diet. This aspect must be considered in food supplementation and fortification programs.